Diagnostic Challenges in Ovarian Hyperthecosis: Clinical Presentation with Subdiagnostic Testosterone Levels - Sanket Shah; Callie Torres; Naser Gharaibeh (Case Reports in Endocrinology)
Symptoms of hyperandrogenism and virilization in postmenopausal women warrant workup for ovarian hyperthecosis. In this case series, we discuss two patients who presented with symptoms of hyperandrogenism and metabolic abnormalities including insulin resistance stemming from ovarian hyperthecosis. Imaging revealed normal ovaries in both patients. However, both patients had total serum testosterone levels below the lower diagnostic limit for ovarian hyperthecosis. Due to high clinical suspicion of ovarian hyperthecosis, both patients underwent bilateral oophorectomy without venous sampling for ovarian androgens. The diagnosis of ovarian hyperthecosis was confirmed on histological examination. Both women had improvement in their hyperandrogenic symptoms, testosterone levels, and biochemical features of insulin resistance after surgical intervention. This presentation of ovarian hyperthecosis with subdiagnostic total serum testosterone levels demonstrates the need for continued research into the pathophysiology of the disease, discussion of the diagnostic threshold of total serum testosterone, as well as the inclusion of ovarian hyperthecosis in the differential of postmenopausal women with hyperandrogenism and insulin resistance.